Mechanism identification of Ficus Deltoidea aqueous extract in rat uterine contractions - Farah Wahida Ibrahim; Nor Idayu Derased; Umi Romaizatul Amiera Zainudin; Nor Fadilah Rajab (Penerbit Universiti Kebangsaan Malaysia, 2018)
Ficus deltoidea or ‘mas cotek,’ is a uterotonic herb traditionally consumed by women to improve menstrual circulation, assist labour, remove retained placenta and treat postpartum bleeding. The aim of the study was to elucidate the mechanism of F. deltoidea in uterine contraction. Crude extracts from 2 different variants of F. deltoidea were used in the study; F. deltoidea var. Deltoidea (FDD) and F. deltoidea var. Angustifolia (FDA). This study was conducted ex vivo on the strips of isolated rats uterus treated with either FDD or FDA aqueous extract with increasing concentrations ranging from 10 μg/ml until 1280 μg/ml at time intervals of 5 minutes between doses. The frequency and intensity of the uterine contractions were monitored via Powerlab software. Maximum contractions for both extracts were identified, recorded and the uterine strips samples at maximum contraction were selected and homogenized in order determine the role of prostaglandin F2α (PGF2α) in the mechanism of uterine contraction. Other than that, phosphorylated 42/44 (p42/44) of mitogen activated protein kinase (MAPK) expression was also detected via immunoblotting. The results showed that the maximum contraction induced by FDD was at the concentration of 320 μg/ml, whereas for FDA was at 960 μg/ml. Both FDD and FDA increased the intensity of uterine strips contractions and there were notable trend of increased PGF2α expression as well. Further analysis revealed that the uterine contractions involved the MAPK pathway through the phosphorylation of p42/44 protein. In conclusion, Ficus deltoidea of both variants have the ability to stimulate uterine contraction through the mechanism of MAPK pathway.